An Adaptive Role for Negative Expected Pain in Patients With Neuropathic Pain. Issue 5 (May 2015) - Bostick, Geoff P.; Toth, Cory; Dick, Bruce D.; Carr, Eloise C.J.; Stitt, Larry W.; Moulin, Dwight E.
Abstract : Objectives: To study the relationship between expected pain and future outcomes along with the moderating effects of expected pain in neuropathic pain patients. Methods: Study participants were recruited for the Canadian Neuropathic Pain Database. To examine the relationship between expected pain and 6-month pain intensity, pain-related disability, and catastrophizing, multiple regressions were performed. These relationships were adjusted for potential confounding (age, sex, baseline pain intensity, and psychological distress). To evaluate the moderating effect of expected pain on the relationship between baseline pain intensity and 6-month outcomes, pain intensity×expected pain interaction terms were created. Results: Complete data for analysis was available for 560 patients (71%). Expected pain was positively correlated with pain intensity and pain-related disability scores at 6 months. The relationship between baseline pain intensity and 6-month catastrophizing scores was moderated by expected pain (however, despite a similar trend, expected pain did not statistically moderate the relationship between baseline pain intensity and 6-month pain intensity or disability). At higher levels of pain, predicted catastrophizing scores were higher for those with low levels of expected pain than those with high levels of expected pain. An opposite relationship was observed for patients with the lower levels of pain. Discussion: In neuropathic pain patients whose pain does not respond to therapy, high levels of expected pain may relate to relatively lower catastrophizing scores by shifting focus away from futile attempts at "curing" pain toward focusing on achievement of more realistic personal goals.